2021
DOI: 10.18488/journal.aefr.2021.116.501.511
|View full text |Cite
|
Sign up to set email alerts
|

Illiquidity Premium in the Indian Stock Market: An Empirical Study

Abstract: India has the highest global mean illiquidity ratio (Amihud, Hameed, Kang, & Zhang, 2019), which is the primary motivation for this study. This paper aims to price the traded illiquidity and test the well-documented asset pricing models: the capital asset pricing model and the Fama & French's (1993) three-factor model. The average annual illiquidity premium for the Indian stock market is found to be considerably high when compared to the illiquidity premiums in other developed and developing nations, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…e empirical discourse on the interdependencies among BRICS stock markets is blatant with a strong consensus of high integration [29][30][31]. However, the high integration within the BRIC markets has the potential of minimizing diversification benefits across time-frequencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e empirical discourse on the interdependencies among BRICS stock markets is blatant with a strong consensus of high integration [29][30][31]. However, the high integration within the BRIC markets has the potential of minimizing diversification benefits across time-frequencies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We can classify the relevant studies according to three different strands: first, a group of studies found the presence of partial or incomplete integration of equity markets in BRICS economies (Al-Mohamad et al, 2020; Bai, 2008; Prakash et al,. 2017; Sharma et al, 2013; Singh & Sharma, 2012); second, another group of studies demonstrated presence of stronger and increasing integration among the BRICS stock markets (Bai, 2009; Bhar & Nikolova, 2009; Dasgupta, 2014; Joshi, 2013); and third, a few studies found no integration among the BRICS capital markets (Jeyanthi, 2012; Ouattara, 2017; Singh & Kaur, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To eliminate diversification problems and maintain an adequate number of firms when calculating factors, constructing different portfolios, and testing asset pricing models, we closely followed the methodology suggested by Fama and French (1993), Fama and French (2008) and Fama and French (2015). Firms with no R&D expenditure, negative P/B ratios, and missing adjusted closing prices during the year were excluded from the data set to avoid any survivorship bias (Kundlia & Verma, 2021;Lin & Wang, 2016). As a result, the final sample included an average of 524 firms per year during the sample period.…”
Section: Datamentioning
confidence: 99%